COMPARATIVE ANALYSIS OF TOWER BASE TRANSCEIVER STATION (BTS) FOOT 4 BETWEEN BRACING TYPE V WITH BRACING TYPE X - Sumaidi (Journal of Civil Engineering Science and Technology (CI-TECH), 2020)
This paper explains the comparison 4-foot Base Transceiver Station (BTS) towers between type v bracing and type x bracing in terms of strength and economic aspects using SAP 2000 applications. As technology develops, people's desire for good telecommunications technology is enhancement. The writer analyzes the tower with type v bracing and type x bracing using the SAP 2000 application. BTS towers are used with a height of 25 meters, width of 6 meters, length of 6 meters, height of each segment of 2.5 meters. Then analyze the strengths using the SAP 2000 application based on the TIA / EIA 1991 standard with displacement not exceeding H/200. After the SAP 2000 application is finished running, the results of the building's own weight output are used for economic comparisons. The results of type v bracing analysis obtained a displacement of 0.4 millimeters with a building own weight of 123.668 KN. The result of type x bracing analysis obtained a displacement of 0.6 millimeters with a building weight of 143,440 KN. The results of this analysis recommend the BTS tower to use type v bracing instead of using type x bracing.